2021
DOI: 10.3390/nano11010235
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Calcium Oxalate Precursors during the Pre- and Post-Nucleation Stages with Poly(acrylic acid)

Abstract: In this work, calcium oxalate (CaOx) precursors were stabilized by poly(acrylic acid) (PAA) as an additive under in vitro crystallization assays involving the formation of pre-nucleation clusters of CaOx via a non-classical crystallization (NCC) pathway. The in vitro crystallization of CaOx was carried out in the presence of 10, 50 and 100 mg/L PAA by using automatic calcium potentiometric titration experiments at a constant pH of 6.7 at 20 °C. The results confirmed the successful stabilization of amorphous ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
(51 reference statements)
1
10
0
Order By: Relevance
“…Since calcium ions that are sequestered by PAA are not detected by the probe, the ion-complexing behavior of the PAA could be measured. As seen in Figure a, the measured free Ca 2+ concentration decreases as the solution concentration of PAA increases, which is consistent with studies of Ca 2+ titration into a PAA-containing solution . Three PAA molecular weights were used for this study (1.8, 100, and ∼250 kDa, abbreviated as PAA 1.8 , PAA 100 , and PAA 250 ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Since calcium ions that are sequestered by PAA are not detected by the probe, the ion-complexing behavior of the PAA could be measured. As seen in Figure a, the measured free Ca 2+ concentration decreases as the solution concentration of PAA increases, which is consistent with studies of Ca 2+ titration into a PAA-containing solution . Three PAA molecular weights were used for this study (1.8, 100, and ∼250 kDa, abbreviated as PAA 1.8 , PAA 100 , and PAA 250 ).…”
Section: Resultssupporting
confidence: 89%
“…As seen in Figure 5a, the measured free Ca 2+ concentration decreases as the solution concentration of PAA increases, which is consistent with studies of Ca 2+ titration into a PAA-containing solution. 46 Three PAA molecular weights were used for this study (1.8, 100, and ∼250 kDa, abbreviated as PAA 1.8 , PAA 100 , and PAA 250 ). For PAA 100 and PAA 250 , more than 50% of available calcium is sequestered when the PAA concentration is 1000 μg/mL.…”
Section: Mechanism Of Mineralization Inhibitionmentioning
confidence: 99%
“…A number of patients suffered from pathological biomineralization such as kidney stones and gallstones, and few useful prevention methods could be applied. Díaz-Soler et al (2021) found that calcium oxalate precursors, which are the main component of kidney stones, could be stabilized by polyacrylic acid (PAA) by forming an LLPS-dependent PILP process. They found that PAA could stabilize the multi-ion complexes, and so that delaying the nucleation process.…”
Section: Bionic Applicationsmentioning
confidence: 99%
“…The COD form is often present in the urine of healthy subjects while COM calculi are more prevalent in the urine of recurrent stone formers compared with urine from healthy subjects [14,15]. Thus, recent reports focused on how natural and synthetic additives, for example, amino acids [16][17][18][19], polymers [20,21], lipids [22], proteins [23,24], peptides [25,26], metal ions [27][28][29], and carboxylic acids [30,31], affect the formation of the different forms of CaOx and how they can be leveraged to prevent or treat kidney stones. Various additives show specific binding with different surfaces of the CaOx crystals and can inhibit their growth via various mechanisms [32].…”
Section: Introductionmentioning
confidence: 99%